Tren dan Masa Depan Inovasi Pendidikan - Ummi Aisyatus Salehah Ahlul Jannah; Mutiatul Hasanah; Agus Wedi (STIKes Ibnu Sina Ajibarang, 2025)
The development of digital technology such as Society 5.0, Internet of Things (IoT), and Big Data and Machine Learning have brought major changes to the world of education, especially in forming a more responsive, inclusive, and adaptive learning system. This study aims to examine the trends and future potential of technology-based educational innovations, especially at the elementary school level. The method used is a literature study with a qualitative descriptive approach, through a review of literature from various current scientific sources. The results of the study show that Society 5.0 encourages the transformation of the role of teachers and student learning patterns, IoT increases interactivity and efficiency in the learning process, and Big Data and Machine Learning enable the implementation of adaptive learning that is in accordance with the needs of individual students. However, the implementation of this technology also faces challenges such as limited infrastructure, teacher readiness, and data security. Therefore, the integration of technology in education needs to be carried out wisely, gradually, and involves the collaboration of all stakeholders.